Gambaran Sedimen Urin pada Orang Lanjut Usia yang Mengalami Hipertensi - Dini Sartika (Jaringan Laboratorium Medis, 2020)
Elderly was a person who reaches the age more than 60 years that susceptible by the aging, such as hypertension. Hypertension was one of the factor for kidney disease. Hypertension is a disease that has systolic blood preasure up to 140 mmHg and diastolic up to 90 mmHg. Find out how the description of urine sediment in older people with hypertension. Type of descriptive type,include data collection, processing and presentation of data. Samples were taken as many 25 people with criteria for elderly people affected by hypertension. Urine examination is carried out by the Malbin-Streinheimer painting method. The result showed 19 people (76%) had hematuria or the possibility of infection and 6 people (24%) did not have hematuria.from the examination also obtained a cylinder of 6 people, namely 4 people (16%) 1/Lpb and 1/Lpb 2 people (8%). This cylinder provides an overview of kidney abnormalities. Urine sediment examination in elderly people with hypertension gives an overview of renal hypertension with discovery of a cylinder accompanied by microscopic hematuri.